BO’LAJAK PEDAGOGLARDA KASBIY VA KOGNITIV KOMPETENSIYALARINI RIVOJLANTIRISH TEXNOLOGIYALARI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article is devoted to the theoretical and practical analysis of modern technologies for developing the professional and cognitive competencies of future teachers. The study highlights the mechanisms for forming key competencies such as professional maturity, critical and creative thinking, independent decision-making in problematic situations, a reflective approach, and digital literacy. The article presents opportunities for enhancing the professional capacity of future teachers through the application of a competency-based approach to educational process design, including interactive methods, problem-based learning, project-based learning, digital platforms, simulation-based training, and metacognitive strategies.Furthermore, innovative pedagogical technologies aimed at activating cognitive processes (analysis, synthesis, evaluation, and reflection) are systematically substantiated. The research findings indicate that an educational environment organized on the basis of an integrative and technological approach contributes not only to the formation of solid theoretical knowledge but also to the development of practical skills, flexible thinking, and professional identity among future teachers.This article includes scientific and practical recommendations aimed at modernizing the teacher training process, improving the quality of education, and preparing innovative-thinking specialists.